Strategies For Building Integrity In Improving Company Productivity And Performance - Purwanggono, Cuk Jaka (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Integrity in the business world is a crucial aspect in maintaining the sustainability and success of a company amidst increasing competition and the ever-changing dynamics of the market. This research aims to delve deeper into the strategies that companies can implement to build integrity as a foundation for enhancing their productivity and performance. The study is conducted through a literature review method. The study results indicate that a company's success based on integrity has a positive impact on the trust of stakeholders. Companies recognized for high integrity tend to gain the trust of customers, business partners, employees, and investors. Conversely, ethical violations or dishonesty can damage reputation and cause serious impacts on financial performance and brand image. In facing the complexity of modern business, strategies for building integrity involve ethical leadership as an example, the establishment of an integrity-based organizational culture, supervision and monitoring systems, ethics education and training, technology implementation, transparency, accountability, as well as continuous assessment and improvement. Integrity, productivity, and company performance are closely intertwined, forming a solid foundation for organizational sustainability and success. By understanding strategies for building integrity, it is hoped that companies can optimize their integrity, create a competitive advantage, and ultimately enhance overall productivity and performance. This research provides a comprehensive perspective for business stakeholders, researchers, and practitioners in the context of building integrity in an ever-changing business era.